Preparation method of fibrous Cu catalyst and application of fibrous Cu catalyst in carbon dioxide electrocatalytic reduction
By using low-cost raw materials such as Cu(NO3)2·3H2O, melamine, sucrose, etc., a fibrous Cu catalyst without substrate support was prepared through a pyrolysis procedure, which solved the problems of complex catalyst preparation and low product selectivity in the prior art, and achieved efficient conversion of CO2 to formic acid.
Patent Information
- Application Number
- CN202411715421.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
AI Technical Summary
The existing fibrous or dendritic copper catalyst preparation methods and equipment have high requirements, complex preparation process, and have failed to effectively convert CO2 into formic acid by using pure Cu catalysts, and the product selectivity is low.
The low-cost raw materials Cu(NO3)2·3H2O, melamine and sucrose were used to regulate Cu morphology through pyrolysis procedures to prepare a fibrous Cu catalyst without substrate support.
The main product of this catalyst in CO2 electrocatalytic reduction is formic acid, with a Faraday efficiency of 26.3%, which simplifies the preparation process and reduces equipment requirements.
Smart Images

Figure CN119615233A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of Cu catalyst materials and the catalytic application field thereof, and in particular to a method for preparing a fibrous Cu catalyst and the application thereof in the electrocatalytic reduction of carbon dioxide. Background Art
[0002] The capture, storage and conversion technology of CO2 has always received widespread attention. Among them, CO2 electrocatalytic reduction (CO2ER) has important academic research value and potential industrial application prospects because it can utilize excess electricity from new energy sources and convert CO2 into energy products or important chemical raw materials under mild conditions.
[0003] As an excellent hydrogen storage material and fuel for fuel cells, formic acid is considered to be a CO2 reduction product with excellent added value (Chem. Rev. 2019, 119, 7610-7672). In the CO2ER catalyst system, Sn, Pb, In, and Bi are considered to be catalysts for producing formic acid (Materials Today, 2023, 67, 320). In CO2ER, the Cu catalyst has special properties because it can catalyze the reduction of CO2 to CC coupling products. However, there are few studies focusing on the conversion of CO2 into formic acid by Cu catalysts. However, unmodified Cu bulk materials (bulk Cu) usually face problems such as high overpotential and low product selectivity. To meet these challenges, researchers have carried out extensive and in-depth research on the structural design and modification of Cu catalysts, and have achieved some results.
[0004] Defei Liu et al. used the non-solvent induced phase separation (NIPS) process to prepare a Cu hollow fiber preform by spinning Cu powder, pyrrolidone, polysulfone binder and polypyrrolidone as raw materials, and then sintered and reduced the preform in air atmosphere (200 mL / min) and hydrogen / argon (2:8, 100 mL / min) to obtain a Cu hollow fiber catalyst. Under the conditions of 0.1 M KHCO3, -0.7 V (vs RHE), 10 mL min -1CO2, the Faraday efficiency of formic acid is about 50%; Abhijit Dutta et al. used 1.5M sulfuric acid solution as the medium and 0.2M copper sulfate as the electrodeposition raw material, and modified and grew a dendritic copper catalyst on a Cu sponge substrate by electrodeposition. Under 0.5M NaHCO3, -0.7V (vs RHE) conditions, the Faraday efficiency of formic acid reached 25%; Pengsong Li et al. used Cu-EDTA as the copper precursor salt and NaBH4 as a strong reducing agent to prepare a Cu aerosol network with a crystal defect structure. The product distribution test showed that the main product corresponding to the catalyst was the C1 reduction product CO, and the Faraday efficiency of formic acid was close to 20% (1M KOH, -0.8V vs RHE).
[0005] The existing preparation of fibrous or dendritic copper catalysts has high requirements for equipment and complex preparation processes. For example, Cu hollow fiber catalysts require a spinning process and must undergo two pyrolysis processes in air and hydrogen; some dendritic Cu catalysts require a substrate support, such as using foam copper or copper foil as a substrate and using electrochemical deposition to grow the catalyst. Since the melting point of metal Cu is only 1083°C, its Tammann and Hüttig temperatures are 405°C and 324.9°C respectively, it is easy to sinter during the pyrolysis process. It is very challenging to prepare fibrous copper catalyst materials using only high-temperature pyrolysis methods, and they will generally agglomerate into large Cu particles.
[0006] As an excellent hydrogen storage material and fuel cell fuel, formic acid is considered to be a CO2 reduction product with excellent added value. However, there is little research on the conversion of CO2 into formic acid using Cu catalysts, especially pure Cu catalysts.
[0007] In view of the existing technical defects, the present invention aims to develop a method for a fibrous copper catalyst with low equipment requirements, simplified preparation process, and no substrate support. In view of the fact that there are few studies on the conversion of CO2 to formic acid by Cu catalysts, especially pure Cu catalysts, the present invention focuses on the activity and selectivity of Cu catalysts for formic acid in CO2ER, providing new research ideas for the field of CO2 electrocatalytic conversion. Summary of the invention
[0008] The purpose of the present invention is to overcome the shortcomings of the prior art, discloses a method for preparing a fibrous Cu catalyst and its application in the electrocatalytic reduction of carbon dioxide, utilizes conventional operating methods, uses low-cost raw materials Cu(NO3)2·3H2O, melamine and sucrose, and through a pyrolysis process, the pyrolysis gas of the melamine and sucrose mixture regulates the Cu morphology to obtain a fibrous Cu catalyst material without substrate support, the main CO2ER product of the catalyst is formic acid, and the Faraday efficiency is 26.3%; the present invention focuses on developing the activity and selectivity of formic acid in the three-dimensional fibrous Cu catalyst in CO2ER, formic acid is considered to be an excellent hydrogen storage material and fuel cell fuel, and is a CO2 reduction product with excellent added value; it provides new research ideas for the field of CO2 electrocatalytic conversion, and has excellent promotion and application prospects.
[0009] To achieve the above purpose, the technical solution adopted in this application is:
[0010] A method for preparing a fibrous Cu catalyst comprises the following steps:
[0011] Step S1: weigh sucrose and Cu(NO3)2·3H2O, dissolve them in deionized water, stir at room temperature, remove water from the dissolved solution, and further dry to obtain an emerald green powder sample;
[0012] Step S2: weigh melamine and the emerald green powder sample of step S1, grind and mix them evenly;
[0013] Step S3: Pyrolyze the sample ground and mixed in step S2. The pyrolysis gas is an inert gas. The temperature is raised according to the pyrolysis program. The initial temperature is 30°C and the final temperature is kept at 750°C. The temperature is then lowered to obtain a fibrous Cu catalyst.
[0014] Furthermore, in step S1, the mass ratio of sucrose to Cu(NO3)2·3H2O is 1:3.5 to 1:6.8.
[0015] Furthermore, in step S1, the mass ratio of sucrose to deionized water is 0.2:50; stirring is performed at room temperature for 1 hour.
[0016] Furthermore, the temperature during room temperature stirring in step S1 is 65°C to 70°C.
[0017] Furthermore, in step S1, water is removed by rotary evaporation, and then the mixture is connected to a vacuum oil pump for further drying.
[0018] Furthermore, the mass ratio of melamine in step S2 to the emerald green powder sample in step S1 is 3:1 to 5:1.
[0019] Furthermore, in step S3, pyrolysis is carried out in a tubular furnace, the pyrolysis gas is Ar, and the pyrolysis program is: the initial temperature is 30°C, increased to 80°C at 3°C / min, maintained for 1h, increased to 550°C at 3°C / min, maintained for 2h, increased to a final temperature of 750°C at 3°C / min, maintained for 2h.
[0020] Furthermore, the Ar flow rate is 50 mL / min.
[0021] A fibrous Cu catalyst is prepared by any one of the above preparation methods.
[0022] A use of a fibrous Cu catalyst in the electrocatalytic reduction of carbon dioxide, wherein the catalyst is prepared by any one of the above preparation methods.
[0023] The beneficial effects of the present invention are:
[0024] 1) The present invention utilizes conventional operation methods, uses low-cost raw materials Cu(NO3)2·3H2O, melamine, and sucrose, and obtains a substrate-free fibrous Cu catalyst material by pyrolysis in a tubular furnace. The main CO2ER product of the catalyst is formic acid, and the Faraday efficiency is 26.3% (-0.6V vs RHE, 0.5M KHCO3). Formic acid is considered to be an excellent hydrogen storage material and fuel cell fuel, and is a CO2 reduction product with excellent added value. It provides new research ideas for the field of CO2 electrocatalytic conversion and has excellent promotion and application prospects.
[0025] 2) The formation of fibrous Cu is mainly attributed to the regulation of Cu morphology by the pyrolysis gas of melamine and sucrose mixture, in addition to the amount of Cu(NO3)2·3H2O used. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of Sample 1 in the examples of this application;
[0027] Figure 2 This is the SEM image of Sample 2 in the examples of this application;
[0028] Figure 3 This is the SEM image of Sample 3 in the examples of this application;
[0029] Figure 4 This is the XRD characterization diagram of Sample 3 in the examples of this application;
[0030] Figure 5 This is the LSV test curve of Sample 1 in the embodiment of this application;
[0031] Figure 6This is the LSV test curve of Sample 2 in the embodiment of this application;
[0032] Figure 7 This is the LSV test curve of Sample 3 in the embodiment of this application;
[0033] Figure 8 This is the Faraday efficiency diagram of the CO2ER product of Sample 3 in the examples of this application;
[0034] Fig. 9 The CO2ER liquid phase product of Sample 3 at -0.6vs RHE (V) in the example of this application 1 H NMR spectra. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings, and the protection scope of the present invention is not limited to the following:
[0036] Example 1: Catalyst preparation
[0037] Step S1:
[0038] Weigh 0.2 g of sucrose, 700 mg or 900 mg or 1.359 g of Cu(NO3)2·3H2O, dissolve them in 50 mL of deionized water, and stir at room temperature for 1 h; remove moisture by rotary evaporation of the dissolved solution at 65°C to 70°C in a water bath, and then connect the solution to a vacuum oil pump for further drying to obtain an emerald green powder sample.
[0039] Step S2:
[0040] Weigh 3 g of melamine and grind and mix the powder sample in step 1 evenly;
[0041] Step S3:
[0042] The ground and mixed samples were placed in a porcelain boat and pyrolyzed in a tube furnace. The pyrolysis gas was Ar (50 mL / min). The pyrolysis program was an initial temperature of 30°C, raised to 80°C at 3°C / min, maintained for 1 h, raised to 550°C at 3°C / min, maintained for 2 h, raised to a final temperature of 750°C at 3°C / min, maintained for 2 h, and cooled. The catalysts obtained were named Sample 1 (700 mg), Sample 2 (900 mg), and Sample 3 (1.359 g) in order of the amount of Cu(NO3)2·3H2O input.
[0043] Example 2: Catalytic performance test
[0044] Step 1: Linear Sweep Voltammetry (LSV)
[0045] Linear voltammetry was used to test the activities of catalysts Sample 1, Sample 2, and Sample 3.
[0046] Preparation of working electrode: 400 μL of ethanol, 58 μL of water, and 42 μL of Nafion solution were mixed, and 5 mg of Sample 1, Sample 2, and Sample 3 were dispersed in the mixed solution, respectively, and ultrasonicated for 30 min to obtain three kinds of slurries. Then, 45 μL of the slurries were measured and deposited on the surface of a glassy carbon electrode with a diameter of 3 mm in batches to obtain different working electrodes;
[0047] An H-type electrolytic cell was used, with an Ag / AgCl electrode as the reference electrode, a Pt sheet electrode as the counter electrode, and a three-electrode system formed with the working electrode. A 0.5 mol / L KHCO3 solution was used as the electrolyte. The test was carried out at -0.8 to -1.8 V vs Ag / AgCl. The LSV curves were tested under Ar and CO2 saturated atmospheres, respectively, with a scan rate of 5 mV / s.
[0048] Step 2: Constant Potential Test
[0049] Preparation of working electrode: 800 μL of ethanol, 117 μL of water, and 83 μL of Nafion solution were mixed, and 10 mg of Sample 1, Sample 2, and Sample 3 were dispersed in the mixed solution respectively. Ultrasonication was performed for 30 min to obtain slurry. 2×100× μL of slurry was measured and deposited on the front and back sides of a carbon paper electrode with a diameter of 1.2 cm in batches to obtain different working electrodes.
[0050] Using an H-type micro-electrolytic cell, with an Ag / AgCl electrode as the reference electrode, a Pt sheet electrode as the counter electrode, and a 0.5 mol / L KHCO3 solution as the electrolyte, the electrolysis reaction was carried out at -1.22V, -1.32, and -1.42V vs Ag / AgCl. A CO2 atmosphere was introduced into the three-electrode system at a CO2 flow rate of 20mL / min. The product Faraday efficiency was obtained by constant potential (-0.6 to -0.8V vs RHE) testing, gas chromatography was used to monitor the quantitative gas phase products, and nuclear magnetic resonance was used to quantify the liquid phase products. The product distribution at -0.6 to -0.8V vs RHE was preliminarily investigated.
[0051] Example 3: Structural characterization of Sample 1, Sample 2, and Sample 3
[0052] The SEM characterization results of Sample 1, Sample 2, and Sample 3 are as follows: Figure 1-Figure 3 Display, such as Figure 1As shown in Figure 1, when the amount of Cu(NO3)2·3H2O is small, the sample morphology after pyrolysis shows irregular particles (Sample 1). Figure 2 As shown in Figure 2, further increasing the amount of Cu(NO3)2·3H2O, the pyrolyzed sample Sample 2 is granular, and the Cu particles tend to grow into fibers, but the structure is still dispersed in the carbon medium, as shown in Figure 2. Figure 3 As shown in Figure 2, when the amount of Cu(NO3)2·3H2O increases to the maximum (1.359 g), the obtained sample (Sample 3) exhibits a three-dimensional fibrous structure, as shown in Figure 2. Figure 4 The XRD characterization diagram of Sample 3 of the present invention is shown in FIG. The reason for the morphological evolution of the above samples is that when the Cu salt is less, Cu 2+ Dispersed in the mixture of sucrose and melamine, the particles formed during the pyrolysis process are separated or even wrapped by the formed carbon, so Sample 1 presents an irregular particle morphology; when the amount of Cu salt is further increased, some Cu particles are not separated and wrapped by carbon, and they will fuse during the pyrolysis process, so Sample 2 presents both Cu particles and a strip structure after a small amount of Cu particles are fused; when the amount of Cu(NO3)2·3H2O is increased to the maximum, the carbon formed by the pyrolysis of sucrose and melamine in Sample 3 is not enough to wrap and separate the Cu species, so the Cu particles gradually fuse and connect to form a three-dimensional fibrous morphology.
[0053] Example 4: LSV test results of Sample 1, Sample 2, and Sample 3
[0054] like Figure 5-Figure 7 As shown in the figure, LSV was used to investigate the activity of the samples. By comparing the current density differences of different catalysts under Ar and CO2 atmospheres, it can be seen that Sample 1 has no CO2 electrocatalytic reduction activity, while Sample 2 and Sample 3 have catalytic activity, among which the catalytic activity of Sample 3 is more significant.
[0055] Example 5: Constant Potential Test Results of Sample 3
[0056] like Figure 8 and Fig. 9 As shown in the figure, the product distribution and Faraday efficiency of Sample 3 were investigated. The results showed that the main CO2 reduction product was formic acid (HCOOH). When the reduction potential was -0.6 vs RHE (V), the Faraday efficiency was 26.3%. Hydrogen was the product of the hydrogen evolution side reaction. As the reduction potential increased, the hydrogen evolution side reaction intensified and the Faraday efficiency of formic acid decreased.
[0057] Comparative Example 1:
[0058] Using Sample 3 as the benchmark:
[0059] Step S1:
[0060] Weigh 0.2 g of sucrose and 1.359 g of Cu(NO3)2·3H2O, dissolve them in 50 mL of deionized water, and stir at room temperature for 1 h; the dissolved solution is rotary evaporated in a water bath at 65°C to 70°C to remove moisture, and then connected to a vacuum oil pump for further drying to obtain an emerald green powder sample.
[0061] Step S2:
[0062] Weigh 3 g of melamine and grind and mix the powder sample in step 1 evenly;
[0063] Step S3:
[0064] The ground and mixed samples were placed in a porcelain boat and pyrolyzed in a tube furnace. The pyrolysis gas was Ar (50 mL / min). The pyrolysis program was an initial temperature of 30°C, which was increased to a final temperature of 750°C at 3°C / min, maintained for 2 hours, and then cooled. The obtained catalyst was named Sample 4 (1.359 g);
[0065] Test results:
[0066] The product distribution and Faradaic efficiency of Sample 4 were investigated. The results showed that the main CO2 reduction product was formic acid (HCOOH). When the reduction potential was -0.6 vs RHE (V), the Faradaic efficiency was 5.3%.
[0067] In summary, the present invention discloses a method for preparing a fibrous Cu catalyst and its application in the electrocatalytic reduction of carbon dioxide. The conventional operation method is used, and low-cost raw materials Cu(NO3)2·3H2O, melamine, and sucrose are used. Through a pyrolysis procedure, the pyrolysis gas of the melamine and sucrose mixture is used to regulate the Cu morphology, thereby obtaining a fibrous Cu catalyst material without substrate support. The main CO2ER product of the catalyst is formic acid, and the Faraday efficiency is 26.3%. The present invention focuses on developing the activity and selectivity of formic acid in the three-dimensional fibrous Cu catalyst in CO2ER. Formic acid is considered to be an excellent hydrogen storage material and fuel cell fuel, and is a CO2 reduction product with excellent added value. It provides new research ideas for the field of CO2 electrocatalytic conversion and has excellent promotion and application prospects.
[0068] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.
Claims
1. A method for preparing a fibrous Cu catalyst, characterized in that: The preparation method comprises the following steps: Step S1: weigh sucrose and Cu(NO3)2·3H2O, dissolve them in deionized water, stir at room temperature, remove water from the dissolved solution, and further dry to obtain an emerald green powder sample; Step S2: weigh melamine and the emerald green powder sample of step S1, grind and mix them evenly; Step S3: Pyrolyze the sample ground and mixed in step S2. The pyrolysis gas is an inert gas. The temperature is raised according to the pyrolysis program. The initial temperature is 30°C and the final temperature is kept at 750°C. The temperature is then lowered to obtain a fibrous Cu catalyst.
2. A method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: In the step S1, the mass ratio of sucrose to Cu(NO3)2·3H2O is 1:3.5 to 1:6.
8.
3. The method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: In the step S1, the mass ratio of sucrose to deionized water is 0.2:50; stirring is carried out at room temperature for 1 hour.
4. The method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: The temperature during room temperature stirring in step S1 is 65°C to 70°C.
5. The method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: In step S1, water is removed by rotary evaporation, and then the mixture is connected to a vacuum oil pump for further drying.
6. The method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: The mass ratio of melamine in step S2 to the emerald green powder sample in step S1 is 3:1 to 5:
1.
7. The method for preparing a fibrous Cu catalyst according to claim 1, characterized in that: In step S3, pyrolysis is carried out in a tubular furnace, the pyrolysis gas is Ar, and the pyrolysis program is: the initial temperature is 30°C, increased to 80°C at 3°C / min, maintained for 1h, increased to 550°C at 3°C / min, maintained for 2h, increased to a final temperature of 750°C at 3°C / min, maintained for 2h.
8. A method for preparing a fibrous Cu catalyst according to claim 7, characterized in that: The Ar flow rate was 50 mL / min.
9. A fibrous Cu catalyst, characterized in that The catalyst is prepared by any one of the preparation methods of claims 1-8.
10. Use of a fibrous Cu catalyst in the electrocatalytic reduction of carbon dioxide, characterized in that: The catalyst is the catalyst described in claim 9 or a catalyst prepared by any one of the preparation methods in claims 1-8.